2015
DOI: 10.1007/s00415-015-7724-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cortical lesions using DIR and FLAIR in early stages of multiple sclerosis

Abstract: The use of non-routine MRI sequences such as DIR has highlighted the role of gray matter (GM) pathology in multiple sclerosis (MS). The aim of this study was to assess the detection and relevance of cortical lesions (CLs) using MRI in early (<5 years) MS patients. 3D DIR and 3D FLAIR images at 3T from 122 patients [93 relapsing-remitting MS (RRMS), 29 clinically isolated syndrome (CIS)] were scored for CLs by two blinded readers. Patients were divided into two groups depending on the presence or absence of CLs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 39 publications
3
19
1
Order By: Relevance
“…Unusual presenting symptoms were reported in 3.9% of our MS patients, more than a third of which were cognitive deficits and behavioral problems (1.5%), followed by seizures (0.9%). Kolber et al emphasized the role of gray-matter pathology and cortical lesions in early MS, which are believed to precede the appearance of the classic white-matter lesions and systematically correlate with patients’ cognitive complaints and seizures 26. Moreover, the incidence of seizures among MS patients was reportedly higher than that in the general population, and it could be an initial presentation of the disease 27…”
Section: Discussionmentioning
confidence: 99%
“…Unusual presenting symptoms were reported in 3.9% of our MS patients, more than a third of which were cognitive deficits and behavioral problems (1.5%), followed by seizures (0.9%). Kolber et al emphasized the role of gray-matter pathology and cortical lesions in early MS, which are believed to precede the appearance of the classic white-matter lesions and systematically correlate with patients’ cognitive complaints and seizures 26. Moreover, the incidence of seizures among MS patients was reportedly higher than that in the general population, and it could be an initial presentation of the disease 27…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, in many studies a strong association was found between physical disability (measured with EDSS and T25FW scores) and total, regional, and cortical GM volume (Sailer et al, 2003;De Stefano et al, 2003;Chen et al, 2004;Tedeschi et al, 2005;Sanfilipo et al, 2005;Audoin et al, 2006Audoin et al, , 2010Calabrese et al, , 2011Houtchens et al, 2007;Fisher et al, 2008;Henry et al, 2008;Fisniku et al, 2008;Ramasamy et al, 2009;Tao et al, 2009;Anderson et al, 2009;Rudick et al, 2009;Roosendaal et al, 2011;Lavorgna et al, 2014). These associations existed throughout the disease course and (Brex et al, 2001;Calabrese et al, , 2010cCeccarelli et al, 2008;Henry et al, 2008;Ramasamy et al, 2009;Bendfeldt et al, 2009;Audoin et al, 2010;Roosendaal et al, 2011) -CL in up to 36% of patients Kolber et al, 2015) RRMS -Atrophy of cortical GM becomes more evident, in particular of the frontal, temporal and parietal cortices. Thalamic volume loss can be extensive Cifelli et al, 2002;Wylezinska et al, 2003;Sailer et al, 2003;Chen et al, 2004;Pagani et al, 2005;Tedeschi et al, 2005;Carone et al, 2006;Calabrese et al, , 2010aCalabrese et al, ,d, 2011Houtchens et al, 2007;…”
Section: The Relation With Physical Disability Is Strongmentioning
confidence: 95%
“…Thalamic volume loss can be extensive Cifelli et al, 2002;Wylezinska et al, 2003;Sailer et al, 2003;Chen et al, 2004;Pagani et al, 2005;Tedeschi et al, 2005;Carone et al, 2006;Calabrese et al, , 2010aCalabrese et al, ,d, 2011Houtchens et al, 2007;Ceccarelli et al, 2008;Sicotte et al, 2008;Mesaros et al, 2008;Fisniku et al, 2008;Ramasamy et al, 2009;Tao et al, 2009;Battaglini et al, 2009;Bendfeldt et al, 2009;Anderson et al, 2010;Roosendaal et al, 2011; -CL in up to 80% of patients. Most CL in the frontal and temporal lobes, especially in the motor cortex and anterior cingulate (Kutzelnigg et al, 2005;Calabrese et al, , 2010aMainero et al, 2009;Roosendaal et al, 2009;Nelson et al, 2011;Sethi et al, 2013;Kolber et al, 2015) SPMS -Atrophy more widespread, atrophy rate accelerates (Cifelli et al, 2002;Sailer et al, 2003;Chen et al, 2004;Pagani et al, 2005;Tedeschi et al, 2005;Carone et al, 2006;Calabrese et al, , 2010aCalabrese et al, , 2011Houtchens et al, 2007;Ceccarelli et al, 2008;Sicotte et al, 2008;Fisniku et al, 2008;...…”
Section: The Relation With Physical Disability Is Strongmentioning
confidence: 97%
“…MRI is the first choice for the imaging diagnosis of NOM, but the spatial and contrast resolution of conventional MR pulse sequences is not efficient and requires improvement in displaying gray matter lesions (13,14). The 3D-DIR pulse sequence uses pulses that may inhibit the cerebrospinal fluid and white matter signals, better display the gray matter of the brain, improve the sensitivity of gray matter lesions, and identify cortical lesions that may not be detected by conventional MR pulse sequence (1315).…”
Section: Discussionmentioning
confidence: 99%
“…The 3D-DIR pulse sequence uses pulses that may inhibit the cerebrospinal fluid and white matter signals, better display the gray matter of the brain, improve the sensitivity of gray matter lesions, and identify cortical lesions that may not be detected by conventional MR pulse sequence (1315). In the DIR sequence, selecting two TI values (TI1 and TI2) according to the longitudinal relaxation time (T1) of the tissues to be imaged, and in brain scanning, selecting corresponding TI1 and TI2 values may inhibit cerebrospinal fluid and white matter signals at the same time and better display the gray matter of the brain (16,17).…”
Section: Discussionmentioning
confidence: 99%